Discretization Fractional-Order Biological Model with Optimal Harvesting - Barhoom Noor S. Sh.; Sadiq Al-Nassir (Abstract and Applied Analysis)
In this paper, a discretization of a three-dimensional fractional-order prey-predator model has been investigated with Holling type III functional response. All its fixed points are determined; also, their local stability is investigated. We extend the discretized system to an optimal control problem to get the optimal harvesting amount. For this, the discrete-time Pontryagin’s maximum principle is used. Finally, numerical simulation results are given to confirm the theoretical outputs as well as to solve the optimality problem.